DEVIATION FROM RED QUEEN BEHAVIOUR AT STRATIGRAPHIC BOUNDARIES: EVIDENCE FOR DIRECTIONAL RECOVERY - Doran N.A.; Arnold A.J.; Parker W.C.; Huffer F.W. (My University, 2004)
Boundary-defining events influence the evolutionary behaviour of post-extinction survivors. The Cox proportional hazards model takes into account the varying background extinction rates characteristic of boundaries and enables survivorship analysis of post-boundary behaviour. Survivorship results from the Middle Cretaceous to recent planktonic foraminifera reveal two intriguing observations. First, they indicate significantly age-dependent extinction probabilities in populations of species following two boundaries: Cenomanian-Turonian (C-T) and Cretaceous-Tertiary (K-T); the survivors are short lived and show rapid turnover. Characteristics that might mediate this macroevolutionary behaviour are clearly distinct from those that precede the extinction. We hypothesize that the rapid taxonomic turnover during post-extinction macroevolutionary recovery is driven by the lingering expression of 'passport' characteristics, where the primary adaptive value was during the preceding extinction. Second, age-dependency of extinction oscillates through time. Many survivorship curves averaging long-term data have exponential or near-exponential form: suggesting a lack of age-dependence consistent with the Red Queen hypothesis. The boundary events discussed here, analysed in higher-resolution 15 Ma subsets, demonstrate perturbation of some post-extinction populations toward positive age-dependence, and are followed by long intervals suggestive of recovery. Red Queen behaviour, when measured over very long time-spans, appears to be the time-averaged result of these boundary-generated oscillations between short-term positive age-dependence and longer-term return to nearly age-independent Red Queen behaviour.